2010
DOI: 10.1002/mus.21713
|View full text |Cite
|
Sign up to set email alerts
|

History of outcome measures for myasthenia gravis

Abstract: This review illustrates how measurements of clinical status in patients with myasthenia gravis have evolved from clinical descriptions and estimates of mortality rates to more sophisticated evaluative instruments, including numerical rating scales that measure strength, endurance, quality of life, and activities of daily living. The rationale and use of weighting and the importance of patient-reported outcomes are also discussed. The measurement of the steroid-sparing effect of an immunosuppressant is also rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
48
1
4

Year Published

2011
2011
2015
2015

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 91 publications
0
48
1
4
Order By: Relevance
“…SF-36 najčešće se koristi za ispitivanje kvalitete oboljelih od miastenije gravis, ali nije pogodan za istraživani uzorak jer sadržava pitanja koja se ne mogu povezati s osnovnim značajkama bolesti [19]. Nadalje, potrebno je dobiti podatke za zdravu, kontrolnu skupinu ispitanika koja služi kao referentna razina [12], rezultate instrumentalnih mjerenja za oboljele [16,19,20,40] te demografske podatke o oboljelima [mjesto prebivališta, visina dohotka, podaci o terapiji i sl.] [12,14].…”
Section: Upitnikunclassified
See 3 more Smart Citations
“…SF-36 najčešće se koristi za ispitivanje kvalitete oboljelih od miastenije gravis, ali nije pogodan za istraživani uzorak jer sadržava pitanja koja se ne mogu povezati s osnovnim značajkama bolesti [19]. Nadalje, potrebno je dobiti podatke za zdravu, kontrolnu skupinu ispitanika koja služi kao referentna razina [12], rezultate instrumentalnih mjerenja za oboljele [16,19,20,40] te demografske podatke o oboljelima [mjesto prebivališta, visina dohotka, podaci o terapiji i sl.] [12,14].…”
Section: Upitnikunclassified
“…Pojam kvaliteta života definira se samo s medicinskog stajališta, jer uključuje samoprocjenu zdravstenog stanja ispitanika [19]. Prvi upitnici za istraživanje oboljelih od miastenije gravis izrađeni su 1950-ih godina [20]. U ovom istraživanju, kvaliteta života oboljelih od miastenije gravis prikazana je u tablicama [ [12,14,16,18].…”
Section: Stupanj Kvalitete žIvota Oboljelih / Preporuke Za Poboljšanjeunclassified
See 2 more Smart Citations
“…A recent literature review [5] reported on the utilization of outcome measure for MG, focussing only the measures for clinical manifestations that are judged to be immediately evident and relevant for clinicians dealing with an MG patient. The author concluded that, although clinical manifestation are of primary relevance, due to the unique characteristics of MG (i.e.…”
Section: Introductionmentioning
confidence: 99%